Role of Saponins in Plant Defense Against Specialist Herbivores - Mubasher Hussain; Biswojit Debnath; Muhammad Qasim; Bamisope Steve Bamisile; Waqar Islam; Muhammad Salman Hameed; Liande Wang; Dongliang Qiu (Molecules, 2019)
The diamondback moth (DBM), Plutella xylostella (Lepidoptera: Plutellidae) is a very destructive crucifer-specialized pest that has resulted in significant crop losses worldwide. DBM is well attracted to glucosinolates (which act as fingerprints and essential for herbivores in host plant recognition) containing crucifers such as wintercress, Barbarea vulgaris (Brassicaceae) despite poor larval survival on it due to high-to-low concentration of saponins and generally to other plants in the genus Barbarea. B. vulgaris build up resistance against DBM and other herbivorous insects using glucosinulates which are used in plant defense. Aside glucosinolates, Barbarea genus also contains triterpenoid saponins, which are toxic to insects and act as feeding deterrents for plant specialist herbivores (such as DBM). Previous studies have found interesting relationship between the host plant and secondary metabolite contents, which indicate that attraction or resistance to specialist herbivore DBM, is due to higher concentrations of glucosinolates and saponins in younger leaves in contrast to the older leaves of Barbarea genus. As a response to this phenomenon, herbivores as DBM has developed a strategy of defense against these plant biochemicals. Because there is a lack of full knowledge in understanding bioactive molecules (such as saponins) role in plant defense against plant herbivores. Thus, in this review, we discuss the role of secondary plant metabolites in plant defense mechanisms against the specialist herbivores. In the future, trials by plant breeders could aim at transferring these bioactive molecules against herbivore to cash crops.